Moral Conflicts of Organ Retrieval A Case for Constructive Pluralism - II, Charles C. Hinkley (Value Inquiry Book Series ;, 2005)
This book addresses ethical conflicts arising from saving the lives of patients who need a transplant while treating living and dead donors, organ sellers, animals, and embryos with proper moral regard. Our challenge is to develop a better world in the light of debatable values and uncertain consequences.